(untitled) (Research, Society and Development, 2020)
This study is an integrative literature review about complementary therapies and other strategies to treat schizophrenia. The search was carried out in the Virtual Health Library, CAPES, PUBMED and Cocrhane databases, with the descriptor “complementary medicine for schizophrenia”. We considered in this review publications between 2015 and 2020, written in Portuguese, English or Spanish. After applying all inclusion and exclusion criteria, 39 (thirty-nine) publications were selected. Among the analyzed strategies, the practice of Yoga presented more publications. We noted that complementary therapies related to schizophrenia are still under study, to prove how they improve schizophrenia symptoms. Therefore, the advancement and development of such practices, can assist in pharmacological treatment as allies in facing the difficulties related to schizophrenia.